2018
DOI: 10.21037/jtd.2018.01.146
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lung resection volume on risk of primary spontaneous pneumothorax recurrence

Abstract: Background: Thoracoscopic stapled bullectomy is a popular procedure for the treatment of primary spontaneous pneumothorax (PSP) that has a relatively high postoperative recurrence rate. One reason for PSP recurrence is the formation of a new bulla around the staple line. We hypothesized that different resected specimen volumes might cause differences in staple line tension. In this study, we analyzed the relationship between postoperative pneumothorax recurrence and resected lung volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…The findings of the chest X-ray and HRCT were reviewed using the Picture Archiving Communication System. The assessment method of the longest length and the specimen volume are described elsewhere (7). The presence of new bullae and pneumothorax in HRCT was assessed by two thoracic surgeons (C.B.P.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the chest X-ray and HRCT were reviewed using the Picture Archiving Communication System. The assessment method of the longest length and the specimen volume are described elsewhere (7). The presence of new bullae and pneumothorax in HRCT was assessed by two thoracic surgeons (C.B.P.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, numerous etiologies of recurrent pneumothorax following VATS have been proposed. While missed bullae have been recognized as the reason for recurrent pneumothorax following VATS, new bullae formation is now being considered an important etiology (4)(5)(6)(7). We have previously reported that higher tension in the staple line which was associated with bulky resection during VATS, increased the risk of recurrence (7).…”
Section: Original Articlementioning
confidence: 99%
“…Presentation of a tumour as recurrent pneumothorax is not well recognised, yet a few cases of other tumours with similar presentations have been reported in the literature. These include primary pulmonary synovial sarcoma,12 bronchial carcinoid tumour,13 squamous cell lung cancer,14 cystic lung metastases from epithelioid sarcoma,15 mucoepidermoid carcinoma,16 non-small cell lung cancer and diffuse pleural mesothelioma 16. In about 2% of cases with spontaneous pneumothorax, underlying malignancy would be present 17.…”
Section: Discussionmentioning
confidence: 99%
“…As the lung weight increased, new bulla formation was more common [6]. Choi et al [19] estimated lung volume using pathologic specimens and concluded that bulky resection was associated with an increase in recurrence. However, the unique apical space should be considered, so we designed our study to only include patients who underwent apical bullectomy for PSP, and we also considered that the resected lung was originally cone-shaped.…”
Section: Discussionmentioning
confidence: 99%